Factors influencing intracytoplasmic sperm injection (ICSI) outcome in men with azoospermia. (29th January 2013) - Abdel Raheem, Amr; Rushwan, Nagla; Garaffa, Giulio; Zacharakis, Evangelos; Doshi, Alpesh; Heath, Carleen; Serhal, Paul; Harper, Joyce C.; Christopher, Nim A.; Ralph, David
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? The management of patients with non‐obstructive azoospermia (NOA) and some cases of obstructive azoospermia involves testicular sperm extraction (TESE or micro‐dissection TESE) combined with intracytoplasmic sperm injection (ICSI). Several studies have investigated the effect of the male age, the cause of azoospermia, testicular histopathology, the type of sperm used, and the use of pentoxyphilline, on the ICSI cycle outcome in men with azoospermia. The present study showed that none of these factors influenced the ICSI outcome in men with azoospermia, thus once sperm is found in an azoospermic male, no other male factor seems to influence the ICSI outcome. To our knowledge this is the first study to comment on the outcome of ICSI in men with NOA based on testicular histopathology. Objectives To access the effect of: male age, the cause of azoospermia (obstructive azoospermia vs non‐obstructive azoospermia [NOA]), testicular histopathology, the type of sperm used (fresh vs frozen‐thawed), and the use of pentoxyphilline on the intracytoplasmic sperm injection (ICSI) cycle outcome in men with azoospermia. To our knowledge this is the first study to comment on the outcome of ICSI in men with NOA based on testicular histopathology. Patients and Methods A retrospective analysis of 137 testicular sperm extraction‐ICSI cycles performed between 2001–2010, involving 103 men with azoospermia, with 26 couples having repeat cycles. Results Analysis of the results did not show any statistically significant differences in the fertilization, embryo cleavage, clinical pregnancy, live birth and miscarriage rates in relation to the male age, cuase of azoospermia, testicular histopathology, type of sperm used and the use of pentoxyphilline. Conclusion Once sperm is found in a man with azoospermia, no other male factor seems to influence the ICSI outcome.